2018
DOI: 10.1080/19490976.2017.1412908
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 28-day Bifidobacterium animalis subsp. lactis HN019 supplementation on colonic transit time and gastrointestinal symptoms in adults with functional constipation: A double-blind, randomized, placebo-controlled, and dose-ranging trial

Abstract: Bifidobacterium animalis subsp. lactis HN019 (HN019) ameliorates chronic idiopathic constipation. Our aim was to determine the efficacy and safety of 28-day supplementation with 1 × 109 or 1 × 1010 CFU of HN019/day for constipation. A total of 228 adults who were diagnosed with functional constipation according to the Rome III criteria were randomized in a double-blind and placebo-controlled trial. Colonic transit time (CTT), the primary outcome, and secondary outcomes that were measured using inventories—pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 47 publications
6
62
1
1
Order By: Relevance
“…We established an accurate Bayesian statistical model to estimate the bowel movement frequency-increasing effect due to B. longum BB536 intake, and this model revealed which subjects were responders or NRs in this study. This model enabled us to detect shortening of the bowel movement interval due to the intake of B. longum BB536, which is consistent with previous research [15,16]. In addition, because Bayesian estimation of the parameters enabled us to calculate a correct interval, this model achieved accurate quantitative evaluation of the effect of B. longum BB536 intake on bowel movement frequency, which has been difficult to achieve by threshold-based responder estimation [21].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We established an accurate Bayesian statistical model to estimate the bowel movement frequency-increasing effect due to B. longum BB536 intake, and this model revealed which subjects were responders or NRs in this study. This model enabled us to detect shortening of the bowel movement interval due to the intake of B. longum BB536, which is consistent with previous research [15,16]. In addition, because Bayesian estimation of the parameters enabled us to calculate a correct interval, this model achieved accurate quantitative evaluation of the effect of B. longum BB536 intake on bowel movement frequency, which has been difficult to achieve by threshold-based responder estimation [21].…”
Section: Discussionsupporting
confidence: 85%
“…Bifidobacterium is a representative microbial genus of probiotics that is frequently used to regulate bowel movements [10]. Multiple randomized controlled trials have shown that bifidobacteria intake increases bowel movement frequency [11][12][13][14] or shortens gut transit time [15,16]. However, the response to bifidobacteria supplementation varies from subject to subject.…”
Section: Introductionmentioning
confidence: 99%
“…The human gut microbiota is a complex community and is important for the health status of the host . Alterations in the gut microbiota and diet have been found to be associated with the pathogenesis of several human diseases . Probiotic supplementation has been found to be associated with improvements in health and the intestinal microbial composition, and the supplementation of L. fermentum has been shown to modulate the intestinal microbiota in piglets .…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Alterations in the gut microbiota and diet have been found to be associated with the pathogenesis of several human diseases. [36][37][38][39][40] Probiotic supplementation has been found to be associated with improvements in health and the intestinal microbial composition, 24,41 and the supplementation of L. fermentum has been shown to modulate the intestinal microbiota in piglets. 42 As the global composition and the presence of pathogens or beneficial bacteria are relevant to the host's health, we analyzed the composition of the test animals over 13 weeks of feeding of bacterial strains.…”
Section: Discussionmentioning
confidence: 99%
“…and dietary fiber (the preferred nutrients for Clostridium spp.) [81,82]. This strategy tallys with the idea of microbial ecosystems therapeutics, which utilizes a mixture of defined bacteria or core microbiome to treat diseases [83].…”
Section: Efficiencymentioning
confidence: 99%